Mechanisms and Treatments of Pruritus in Primary Biliary Cholangitis - Shah, Raj A.; Kowdley, Kris V. (Seminars in Liver Disease, 2019)
Pruritus is a frustrating and sometimes debilitating symptom that commonly accompanies primary biliary cholangitis (PBC). The mechanism by which this symptom manifests remains elusive but extensive research has now shown that the itch is not just “weak pain” as had been the commonly held belief for decades. As this research now shines a light on the many diverse paths by which pruritus might be experienced, the necessity for a comprehensive approach to the symptom becomes clear. Understanding the interplay between the pathophysiology of PBC and delicately balanced neural circuitry is paramount to guiding the search for definitive treatment. Most relevant to providers today is the efficacy of currently available treatments and the side effects that may accompany them. Anion exchange resins, while remaining an important element in therapy, are no longer the only available medication to arrest pruritus. Rifampin, opioid antagonists, and other adjunctive therapies have quickly become a mainstay. Newer therapies such as the molecular adsorbent recycling system now also have a role in treatment. Increased recognition of these modalities may serve to alleviate the often debilitating pruritus experienced by patient suffering from PBC and might ultimately allow them to live more meaningful lives.
Keywords: pruritus; cholestasis; primary biliary cholangitis